The advantages and disadvantages of online architecture teaching compared to traditional teaching, According to the perspective of professors in colleges of architecture in private universities in Riyadh: إيجابيات التعليم المعماري عن بعد وسلبياته مقارنة بالتقليدي من وجهة نظر الأساتذة بكليات العمارة الأهلية بمنطقة الرياض - Mayas Nadeem Ahmad Taha, (Journal of engineering sciences and information technology, 2021)
The research aims to study and evaluate the positives and negatives associated with applying the techniques of online teaching in the curricula of architectural education in the colleges of Architecture in private universities in Riyadh, it discussed the techniques used in this style and the extent of their efficiency in achieving communication between the parties to the architectural education process and comparing them with the traditional architectural teaching. The research used the descriptive, analytical and comparative approach, using a research questionnaire that was applied on a sample of faculty members and was built on four main axes. The overall tool obtained an arithmetic average of about (4.22) according to the traditional teaching style, with a rating higher than the arithmetic average according to the online teaching style, which reached (3.32). These ratios also differed for all the main axes adopted by the research, the axis of the spatial environment obtained the highest average (4.45), followed by the axis of assessment and examinations with an average of (4.312), then the axis of tools and means of communication and interaction with an average of (4.24) and finally the axis of scientific content with an average of (4.07).These averages were in all axes according to the traditional style higher than those according to the online style results.The result of the research and discussion clarified the most important opportunities offered by the online architectural teaching style, which was flexibility, in addition to several other opportunities that were clear in several places in the research. As for the most prominent challenges that accompanied the online architecture style, they were technical challenges and the issues which are related to the qualification of the staff. In addition to the challenges which concern the interaction mechanisms that are the basis of communication between the teacher and the student in colleges of architecture especially, in the first years in which the student does not possess the skills of drawing and training using engineering programs.